Regulation of argA operon expression in Escherichia coli K-12: cell-free synthesis of beta-galactosidase under argA control. - Kelker, N (1977)
Regulation of argA operon expression in Escherichia coli K-12 was studied in a cell-free, deoxyribonucleic acid-dependent, enzyme-synthesizing system. lambdaAZ-7 deoxyribonucleic acid, which carries a fusion of the lacZ structural gene to the argA operon so that beta-galactosidase synthesis is under argA regulation, was used as the template. To eliminate extraneous readthrough from lambda promoters, lambda repressor was introduced into the synthesis mixtures by preparing the S-30 component from a strain (514X5a-12-29) that carries a multicopy hybrid plasmid (pKB252) containing the lambdacI gene. Under these conditions beta-galactosidase synthesis was repressed 90% by the arginine repressor when a sufficient concentration of L-arginine was present. This repression could be overcome by escape synthesis when the lambdaAZ-7 deoxyribonucleic acid concentration in the synthesis mixtures was increased. Guanosine 3'-diphosphate-5'-diphosphate stimulated beta-galactosidase synthesis from this template.